Content analysis of the human body systems course for the third secondary grade in light of creative thinking skills - Bin Ghaith, Haya Abdulaziz Nasser (Journal of Curriculum and Teaching Methodology, 2025)
The study aimed to analyze the content of the Human Body Systems course for the third secondary grade in light of creative thinking skills in terms of creative thinking requirements and their level of availability, as well as comparing the level of availability of creative thinking skills, which are (fluency, flexibility, originality and elaboration). The study used the content analysis method using the descriptive approach, and the study tool was the content analysis card. In order to analyze the data, the study used frequencies and percentages, and it came up with several results, including that the flexibility skill had the highest frequencies and was ranked first with a medium percentage, while the originality skill had the least frequencies and was ranked fourth with a low percentage. It is recommended that the Human Body Systems course for the third secondary grade contain shapes and mind maps that develop students' fluency skills.
Keywords: Content Analysis; Human Body Systems Course; Creative Thinking Skills; Third Secondary Grade